Dynamics of Mitochondrial RNA-Binding Protein Complex in Trypanosoma brucei and Its Petite Mutant under Optimized Immobilization Conditions - Huang, Zhenqiu (American Society for Microbiology, 2014)
There are a variety of complex metabolic processes ongoing simultaneously in the single, large mitochondrion of Trypanosoma brucei. Understanding the organellar environment and dynamics of mitochondrial proteins requires quantitative measurement in vivo. In this study, we have validated a method for immobilizing both procyclic stage (PS) and bloodstream stage (BS) T. brucei brucei with a high level of cell viability over several hours and verified its suitability for undertaking fluorescence recovery after photobleaching (FRAP), with mitochondrion-targeted yellow fluorescent protein (YFP). Next, we used this method for comparative analysis of the translational diffusion of mitochondrial RNA-binding protein 1 (MRP1) in the BS and in T. b. evansi. The latter flagellate is like petite mutant Saccharomyces cerevisiae because it lacks organelle-encoded nucleic acids. FRAP measurement of YFP-tagged MRP1 in both cell lines illuminated from a new perspective how the absence or presence of RNA affects proteins involved in mitochondrial RNA metabolism. This work represents the first attempt to examine this process in live trypanosomes.